การติดตามอันตรกิริยาของยาในผู้ป่วยนอกที่โรงพยาบาลพระมงกุฎเกล้า - นงลักษณ์ โตรักษา (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purpose of this study were to study rate of potential significant drug interactions and the rate of adverse drug reactions caused by these interactions. The outcome of the program implementation was studies as well. The study was descriptive prospective study, performed at outpatients-pharmacy division Phramongkutklao Hospital, from November 2005 to April 2006. Patients were recruited from whose prescriptions were alerted by drug-drug interaction computerized program, these patients were then referred to pharmacist for monitoring and managing the potential drug interaction problem. The rate of potential significant drug interactions screened by computerized program was 1.8% However 299 patients were screened and monitored by pharmacists using high risk factors. Of these patients, the ratio between male and female was 1:0.9, average age was 61.3 years (range from 18-88), average number of drug items were 7.9 per prescription. The rate of adverse drug reactions caused by these interactions was 8.7%, found in 26 patients. There was no statistically difference in the risks used for screening, including gender, age, serum creatinine as well as number of drug items, between actual and non-actual drug-drug interaction. The object drugs mostly found interaction were digoxin (188 episodes), potassium sparing diuetics (105 episodes) and warfarin (63 episodes), The drugs mostly caused adverse drug reaction were warfarin, potassium-sparing diuretics and digoxin with the rate at 12.3%, 7.0% and 6.7% respectively. There were 25.3% consultations from pharmacist to physicians in 77 patients. By questionnaire surveys, all physicians agreed with this program, 66.7% of them satisfied to the pharmacist s consultations. The implementation of drug-drug interaction screening program with pharmacist monitoring and managing the drug interaction problems can helped preventing and reducing serious ADRs in outpatients.